Iodine deficiency: a nutritional crisis or a matter of speculation? : the perfect discourse - Chikowore, Tinashe Shawn (2021)
During pregnancy, an increase in dietary iodine intake arises due to physiologic adaptation, a phenomenon that is characterised by complex effects that increase metabolic demands and incite hormonal changes. The presence of iodine deficiency (ID) during critical stages of gestation is associated with neurodevelopmental deficits and poses as a risk factor to the development of postpartum depression that can disrupt early mother-infant interaction. A pertinent question is at what stage of pregnancy should pregnant women be advised to take iodine-containing supplements.